2020
DOI: 10.1021/acschemneuro.0c00405
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Disease-Associated P123H and V70M Mutations on β-Synuclein Fibrillation

Abstract: Synucleinopathies are a class of neurodegenerative diseases, including Parkinson's disease (PD), Dementia with Lewy bodies (DLB), and Multiple System Atrophy (MSA). The common pathological hallmark of synucleinopathies is the filamentous α-synuclein (α-Syn) aggregates along with membrane components in cytoplasmic inclusions in the brain. β-Synuclein (β-Syn), an isoform of α-Syn, inhibits α-Syn aggregation and prevents its neurotoxicity, suggesting the neuroprotective nature of β-Syn. However, this notion chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 79 publications
(178 reference statements)
0
11
0
Order By: Relevance
“…Previous in silico and in vitro studies have reported on certain aspects of membrane binding of the synucleins ( Bertoncini et al, 2007 ; Brown et al, 2016 ; Ducas and Rhoades, 2012 ; Middleton and Rhoades, 2010 ; Rao et al, 2009 ; Sharma et al, 2020 ; Sung and Eliezer, 2006 ). Yet, the three synucleins were never compared side by side in a systematic manner, and the in vivo relevance of the findings in the above studies remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Previous in silico and in vitro studies have reported on certain aspects of membrane binding of the synucleins ( Bertoncini et al, 2007 ; Brown et al, 2016 ; Ducas and Rhoades, 2012 ; Middleton and Rhoades, 2010 ; Rao et al, 2009 ; Sharma et al, 2020 ; Sung and Eliezer, 2006 ). Yet, the three synucleins were never compared side by side in a systematic manner, and the in vivo relevance of the findings in the above studies remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…The deleterious effects of these mutations have been shown by cell-and animalbased studies [179,180]. Our group recently showed that under normal physiological conditions, fibrilization and aggregation of β-Syn and its disease-associated mutations did not occur, but an altered microenvironment, such as a decrease in pH and/or presence of heparin, caused them to polymerize [181]. γ-Syn, which shares~55% sequence homology with α-Syn, was initially identified in breast cancer malignancies encoded by a breastcancer-specific gene, BCSG1 [182].…”
Section: Misfolding and Aggregation Of α-Synmentioning
confidence: 97%
“…As illustrated in Figure b, CHG NPs showed visible fluorescence response after the interaction with α-syn fibrils; by contrast, insignificant fluorescence changes were detected in the presence of either Lys or hIAPP fibrils (Figure b). From a comparison of the properties of the above amyloid proteins, it is known that α-syn fibrils and Aβ aggregates are both negatively charged , while both Lys and hIAPP fibrils carry positive charges at physiological conditions (pH 7.4) . This implies that electrostatic interactions play a pivotal role in the recognition and fluorescence response behavior of CHG NPs, which were positively charged (Table S1).…”
Section: Resultsmentioning
confidence: 99%